2013
DOI: 10.1371/journal.pone.0079415
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Cleavage of Type II Restriction Endonucleases on the 2′-O-Methyl Nucleotide and Phosphorothioate Substituted DNA

Abstract: The effects of nucleotide analogue substitution on the cleavage efficiencies of type II restriction endonucleases have been investigated. Six restriction endonucleases (EcoRV, SpeI, XbaI, XhoI, PstI and SphI) were investigated respectively regarding their cleavage when substrates were substituted by 2′-O-methyl nucleotide (2′-OMeN) and phosphorothioate (PS). Substitutions were made in the recognition sequence and the two nucleotides flanking the recognition sequence for each endonuclease. The endonuclease clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…An optimum analog should resist RE cleavage without interfering with polymerization reaction of RCA. From a selecting study, we found phosphorothioate (PS) modification at A5pG6 position can strongly suppress PstI activity, and PS had little effects on RCA efficiency 33 34 . Consequently, we used DP with a PS-modified PstI hexamer in the stem to conduct this coreaction.…”
Section: Resultsmentioning
confidence: 99%
“…An optimum analog should resist RE cleavage without interfering with polymerization reaction of RCA. From a selecting study, we found phosphorothioate (PS) modification at A5pG6 position can strongly suppress PstI activity, and PS had little effects on RCA efficiency 33 34 . Consequently, we used DP with a PS-modified PstI hexamer in the stem to conduct this coreaction.…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes are commonly used for cloning and plasmid linearization. Because the evolution of enzymes with custom restriction endonuclease activity is an attractive area of research, we adapted an optical sensor that was previously developed for use in bulk solution . Accordingly, the sensor consists of a nicked duplex in which enzymatic activity disrupts a fluorophore-quencher pair adjacent to the digestion site (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…2′-F RNA and LNA locks sugar ring in C3′ endopucker conformation and has many advantages such as increasing affinity to RNA target 5,37) and protecting oligonucleotide against nuclease digestion 38) . In our previous study, we also found their applications in regulating endonuclease cleavage efficiency 39,40) . Though 2′-OMeRNA has similar characteristics of the C3′ endopucker conformation, it should be avoided in RCA application since it strongly suppressed RCA efficiency.…”
Section: Discussionmentioning
confidence: 97%